Primary Tuberculous Mastitis: Diagnostic Dilemmas In Radiological Imaging (International Journal of Environmental Sciences, 2025)
Breast tuberculosis (TB), or tuberculous mastitis (TM), is a rare form of extra pulmonary tuberculosis caused by Mycobacterium tuberculosis. Although TB is prevalent worldwide, especially in developing countries, involvement of the breast is uncommon. TM can be primary, with localized breast involvement, or secondary, spreading from other sites. This retrospective observational study reviewed 25 cases of primary TM diagnosed between June 2023 and December 2024. The mean age was 33.91 years, and only 12.5% were lactating women. The common presentations were a painless unilateral breast lump without systemic symptoms like fever, night sweats or weight loss. Other presentations included chronic and repeated afebrile abscesses. Most imaging findings on mammography and ultrasound consisted of irregular, ill-defined heterogeneous masses, often mimicking malignancy. Lesion sizes varied significantly, and sinus formation or fistulous tracts were present in 64% of cases. All lesions were categorized as BIRADS 4 with a wide range of probability for breast cancer. Despite, negative results for acid-fast bacilli (AFB) and Mycobacterium tuberculosis (MTB) on microbiological tests—possibly due to technical limitations or atypical strains—histopathological analysis revealed chronic granulomatous mastitis (GM) in 72% of cases, thereby confirming the diagnosis. GM with caseous necrosis and Langhans giant cells was consistent with TB. In conclusion, breast TB is a rare but challenging entity to diagnose on radiological imaging due to its ability to mimic carcinoma. Clinicians must maintain a high index of suspicion, especially in endemic areas, and rely on histopathology for definitive diagnosis—particularly if PCR and microbiology are both negative—to ensure appropriate management, which is medical in most cases, with surgical intervention reserved for abscess drainage.